Kontribusi Ibu Rumah Tangga Dalam Menopang Perekonomian Keluarga Pada Masa Pandemi Covid-19 Di Desa Padak Guar Kecamatan Sambelia - Huzain Jailani; Farhana Muhammad; Isfi Sholihah; Sopi Yani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The impact of COVID-19 hampered the growth of MSMEs. Micro, Small and Medium Enterprises (MSMEs) are one of the business units that play an important role in the growth and development of the economy in Indonesia. MSMEs are also one of the backers of the economy in Indonesia, especially in lower and middle class society. MSMEs have a strategic role in the government's efforts to overcome poverty and movement, because MSMEs can absorb labor so that the impact caused by not absorbing the workforce in the world of work is reduced. In the world of work in MSMEs, we cannot deny that women also contribute to being a factor in work hardiness. This research aims to; knowing the contribution of housewives in supporting the family economy through Brown Sugar MSMEs in Padak Guar Village, Sambelia District during the Covid-19 Pandemic. This research is a type of qualitative research with a qualitative descriptive approach. Data collection technique; observation, interview, documentation and literature study. Testing the validity of the data; source triangulation, technical triangulation and time triangulation. The data analysis procedure uses data reduction, data presentation, and draws conclusions.The results of this study show that the factors behind housewives working as Brown Sugar SMEs include: a) economic factors, b) educational factors, c) environmental factors, namely the location of the Brown Sugar SMEs where they live, d) social factors. The form of contribution given by housewives in the family; 1) women as wives, 2) women as housewives, 3) women as educators. Contribution of housewives in the family economy during the Covid-19 pandemic, namely additional income earners in the family economy and financial managers in the household. The income contribution of housewives that has been made from Brown Sugar MSMEs is 54.16% in Padak Guar Village, Sambelia District. This means that the contribution of a housewife is able to support the family's economy so that the family's needs are met every day so that the family's economic life increases.